Knitting the Future Story of Indian Women: Preventing Violence, Fostering Development, and Accelerating Empowerment - Ramteke, Prerna S (Udayana Journal of Law and Culture; Vol 1 No 2 (2017): Rights of the Vulnerable GroupsDO - 10.24843/UJLC.2017.v01.i02.p02, 2017)
A number of cases of women’s exploitation in India reflects serious problem in viewing and treating women. This article highlights the issues of women in India that are aimed to describe the violence against women in India that degrades their dignity as a human being, to analyze both conceptual and practical aspects of women, particularly with regards to their role in development and also to discuss the need for accelerating the empowerment of women in India. Some concepts such as the three classical approaches on the relationship between women and development are discussed in this writing. Besides this it also analyzes the present situation faced by Indian women that can potentially become obstacles for their development. In addition, this paper looks at some legal instruments and cases that relates to the legal protection of women in India. It is as a research in the field of Sociology that will be enriched by legal, cultural and economic approaches. It will also highlight about the dreams on the better situation for women in India that are expected to become true and will also encourage women in India to involve in any efforts to knit their future story.